Rhizoma Perennial Peanut - Mary J. Williams; Yoana C. Newman; Ann Blount (EDIS)
Rhizoma perennial peanut is a forage legume available to Florida producers that combines high nutritive value (comparable to alfalfa) with persistence under a wide range of management conditions. It can be used for hay production, silage, or grazing. Find out more in this revised 4-page fact sheet that was written by M.J. Williams, Y.C. Newman, and Ann Blount, and published by the UF Department of Agronomy, July 2011.